2020
DOI: 10.1155/2020/3239471
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Analysis of Urban Expansion Using Remote Sensing Methods and Data: A Case Study of Yangtze River Delta, China

Abstract: Land use in the Yangtze River Delta in 2000 and 2017 was classified by the visual interpretation of Landsat satellite images. Then, these images were overlain with economic and physical geographical data to analyze the urban spatial expansion pattern and its physical constraints and socioeconomic influence factors by employing a combination of transition matrix analysis, expansion intensity indices, and equal-fan analysis. The results showed that from 2000 to 2017, there was a significant increase in built-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Values of less than, equal to, and greater than 0 signify a negative correlation, an independent random distribution, and a positive correlation, respectively [66]. Global spatial autocorrelation can only examine the overall spatial autocorrelation of the study area but cannot determine the agglomeration or dispersion effects in a local area [43]. Therefore, Moran's I for local spatial autocorrelation analysis was used.…”
Section: Spatial Autocorrelationmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of less than, equal to, and greater than 0 signify a negative correlation, an independent random distribution, and a positive correlation, respectively [66]. Global spatial autocorrelation can only examine the overall spatial autocorrelation of the study area but cannot determine the agglomeration or dispersion effects in a local area [43]. Therefore, Moran's I for local spatial autocorrelation analysis was used.…”
Section: Spatial Autocorrelationmentioning
confidence: 99%
“…The YRDR has been considered to be the largest regional economy in China [43]. The regional economic collaborative development in the YRDR is critical to enhancing the comprehensive strength of the urban agglomeration [44].…”
Section: Introductionmentioning
confidence: 99%
“…This, in part, has led to criticism from some sociologists that economists tend to ignore micro-level dynamics and fail to provide policy support for actual regional developments (Martin, 2021;Sun et al, 2022;. Therefore, some scholars, such as Sun et al (2020), have explored the factors affecting industrial progress and technological innovation from both macro and micro perspectives. By studying the building energy efficiency (BEE) innovations, they found that compared with the macro national results, the influencing factors at the regional level are more complex and the industrial agglomeration has an important impact.…”
Section: Economic Studies Of New Energy Industrymentioning
confidence: 99%
“…Many studies have examined the characteristics of the urban expansion from the following aspects. (1) Many scholars have investigated the spatiotemporal characteristics of urban expansion at the individual city level (e.g., Beijing [15], Shanghai [16], Wuhan [17], Nanjing [18], Xi'an [19], and Guangzhou [20]), the regional level (e.g., Yangtze River Delta [21], Pearl River Delta [22], Beijing-Tianjin-Hebei [23], Northeast China [24], and the Middle Reaches of the Yangtze River [25]), and the national level [26]. However, few studies fit into the actual policy of allocating urban land quota according to the administrative status of cities in China and comparatively study the differences of urban expansion characteristics among megalopolises, prefecture-level cities, county-level cities, and counties.…”
Section: Literature Reviewmentioning
confidence: 99%